Issues of recovery of damages caused by undue delay in civil proceedings - Asylbekova , А.А.; Tapakova , В.Б.; Zhumagulov , М.И. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
Today, in civil proceedings, one of the most pressing issues is the recovery of damage caused by the waste of time, unjustified prolongation of judicial proceedings. The author analyzes the effectiveness of the right of persons participating in the case to judicial protection of their legitimate interests and rights in civil proceedings, and the principles of the implementation of consideration of cases within a reasonable time frame. Excessive duration of civil proceedings (undue delay) has a direct impact on both pecuniary and non-pecuniary rights of individuals, including disruption of transactions, freezing of working capital, inflationary losses, additional litigation costs, deterioration of business reputation, psychological distress, and loss of legal certainty. This article examines the issues of recovery of damages caused by undue delay in civil proceedings through the prism of civil liability, procedural guarantees, and international standards of the “reasonable time” requirement. In the context of the limited development of a specific compensation mechanism for excessive length of proceedings in the legal system of the Republic of Kazakhstan, the article proposes several possible models of redress: (1) tort liability through qualification of undue delay as unlawful action or inaction; (2) clarification of mechanisms for compensation of non-pecuniary (moral) damage; (3) preventive measures based on procedural time limits and judicial case management. The study formulates recommendations aimed at harmonizing judicial practice and establishing a dedicated compensatory mechanism.